Proceedings of the Fourth International Joint Conference on Autonomous Agents and Multiagent Systems 2005
DOI: 10.1145/1082473.1082797
|View full text |Cite
|
Sign up to set email alerts
|

Launch commit criteria monitoring agent

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Classical agent architectures such as BDI architectures [64] or reactive and deliberative planning thus have a high application potential in this kind of domains. At the Spaceport Processing System Branch at NASA Kennedy Space Center they have developed an intelligent agent application that processes a ground processing telemetry stream in order to increase situation awareness for the space shuttle count-down experts [70]. The system provides a set of automatic alerts and identifies violation of the launch commit criteria and assist in troubleshooting of possible problems.…”
Section: Space Exploration Applicationsmentioning
confidence: 99%
“…Classical agent architectures such as BDI architectures [64] or reactive and deliberative planning thus have a high application potential in this kind of domains. At the Spaceport Processing System Branch at NASA Kennedy Space Center they have developed an intelligent agent application that processes a ground processing telemetry stream in order to increase situation awareness for the space shuttle count-down experts [70]. The system provides a set of automatic alerts and identifies violation of the launch commit criteria and assist in troubleshooting of possible problems.…”
Section: Space Exploration Applicationsmentioning
confidence: 99%
“…Jess is efficient and excels in many categories. It works with dynamic facts and dynamism in variables and rules and is appropriate for NASA's mission-critical applications as well as many other research areas [46,47].…”
Section: Management Platfroms and Reasoning Systemsmentioning
confidence: 99%
“…Systems for outer spaces are also proposed [59], [67], [68], [69]. Applications include precision agriculture, airport or flight support, and space exploration.…”
Section: Figure 17 Performance Evaluation Of Spd-safe -Response Time (In Ms) Per Request On Embedded Devicesmentioning
confidence: 99%
“…It is concluded that Jess is efficient and handles dynamic facts and dynamism in rules and variables. The engine is suitable for the mission critical technologies of NASA [67] and is applied in several research applications.…”
Section: Figure 17 Performance Evaluation Of Spd-safe -Response Time (In Ms) Per Request On Embedded Devicesmentioning
confidence: 99%